Features of responsibility of future specialists of the socionomic professions as an indicator of their digital competence - Olena Bondarchuk; Valentyna Balakhtar; Olena Gorova; Nina Lytvynenko; Nataliia Pinchuk; Oleh Shmanko; Arnold Kiv; Vasyl Oleksiuk (Academy of Cognitive and Natural Sciences, 2022)
The article dwells on to the study of the responsibility of future specialists of socionomic professions as an important indicator of their digital competence. The role of responsibility as a vital indicator of digital competence of future specialists of socionomic professions was determined, which determines their conscious and responsible activities in the context of obtaining and disseminating information in the digital space, promoting both their own psychological safety alongside psychological safety of other members of the digital community. The results of an empirical study were highlighted, which revealed an insufficient level of both responsibility and cognitive-operational components of digital competence for a significant number of future specialists in socionomic professions. Gender differences in the manifestations of responsibility of future specialists depending on the gender are characterized according to which the female respondents were slightly more responsible for the consequences of dissemination of information than male specialists. The expediency of promoting the development of responsibility of future specialists of socionomic professions as an indicator of their digital competence is stated, which can be provided in a specially organized psychological training.